Geological and climatic influences on mountain biodiversity - Antonelli, Alexandre; Kissling, W Daniel; Flantua, Suzette G A; Bermúdez, Mauricio A; Mulch, Andreas; Muellner-Riehl, Alexandra N; Kreft, Holger; Linder, H Peter; Badgley, Catherine; Fjeldså, Jon; Fritz, Susanne A; Rahbek, Carsten; et al. (Nature geoscience, 2018)
Mountains are key features of the Earth’s surface and host a substantial proportion of the world’s species. However, the links between the evolution and distribution of biodiversity and the formation of mountains remain poorly understood. Here, we integrate multiple datasets to assess the relationships between species richness in mountains, geology and climate at global and regional scales. Specifically, we analyse how erosion, relief, soil and climate relate to the geographical distribution of terrestrial tetrapods, which include amphibians, birds and mammals. We find that centres of species richness correlate with areas of high temperatures, annual rainfall and topographic relief, supporting previous studies. We unveil additional links between mountain-building processes and biodiversity: species richness correlates with erosion rates and heterogeneity of soil types, with a varying response across continents. These additional links are prominent but under-explored, and probably relate to the interplay between surface uplift, climate change and atmospheric circulation through time. They are also influenced by the location and orientation of mountain ranges in relation to air circulation patterns, and how species diversification, dispersal and refugia respond to climate change. A better understanding of biosphere–lithosphere interactions is needed to understand the patterns and evolution of mountain biodiversity across space and time.